2012
DOI: 10.1016/j.fgb.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A Paracoccidioides brasiliensis glycan shares serologic and functional properties with cryptococcal glucuronoxylomannan

Abstract: The cell wall of the yeast form of the dimorphic fungus Paracoccidioides brasiliensis is enriched with α1,3-glucans. In Cryptococcus neoformans, α1,3-glucans interact with glucuronoxylomannan (GXM), a hetero polysaccharide that is essential for fungal virulence. In this study, we investigated the occurrence of P. brasiliensis glycans sharing properties with cryptococcal GXM. Protein database searches in P. brasiliensis revealed the presence of sequences homologous to those coding for enzymes involved in the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 91 publications
3
32
0
Order By: Relevance
“…Fungal extracellular vesicles (EVs) were isolated from culture supernatants as described in a number of studies by sequential centrifugation steps (8,9,11,13,14,35). Briefly, the cells and debris were removed from culture fluids by centrifugation at 5,000 and 15,000 ϫ g (15 min, 4°C).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal extracellular vesicles (EVs) were isolated from culture supernatants as described in a number of studies by sequential centrifugation steps (8,9,11,13,14,35). Briefly, the cells and debris were removed from culture fluids by centrifugation at 5,000 and 15,000 ϫ g (15 min, 4°C).…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, most of the molecules trafficked by fungi to the extracellular milieu lack secretion signals (5-7). Extracellular fungal molecules include numerous proteins (8)(9)(10)(11) but also pigments (12) and polysaccharides (13,14). It is now well accepted that these molecules are at least partially exported to the outer space in EVs (15).…”
mentioning
confidence: 99%
“…This information and the fact that molecules that do not contain any molecular tag directing them to conventional processes of secretion (e.g. polysaccharides and pigments) are components of fungal EV [20, 24, 26, 33] strongly suggests, once more, the participation of unconventional and maybe still unknown mechanisms of secretion and vesicle biogenesis. Therefore, one can conclude that the still embryonic proteomic and biochemical studies on EV produced by fungi revealed the existence of membrane-containing compartments at least composed of lipids, polysaccharides, and proteins that, in general, did not engage the conventional pathway of secretion.…”
Section: Characterization Of Fungal Ev In Different Species: a Grementioning
confidence: 99%
“…The combined use of serology, biochemistry, proteomics, and lipidomics led to the identification of polysaccharides, phospholipids, neutral lipids, and proteins as extracellular vesicle components in fungi [20, 24-26, 33-35, 37, 38]. Therefore, it is now well accepted that fungal EV are carriers of distinct molecules to the extracellular space.…”
Section: Biological Functions Of Fungal Ev: the ‘Virulence Bags’mentioning
confidence: 99%
“…GXM samples had their dimensions determined by dynamic light scattering in a 90Plus/BI-MAS Multi Angle Particle Sizing analyzer (Brookhaven Instruments Corp., NY, USA), as described [13]. The serological reactivity of GXM in the different fractions obtained by ultrafiltration was analyzed by ELISA and dot blot, as previously described [14,20,21]. …”
Section: Methodsmentioning
confidence: 99%